Pengaruh Penerapan Sistem e-Filing, Pengetahuan Perpajakan, Dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Di Kpp Pratama Medan Polonia - Mulyana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This research was conducted with the aim of knowing the effect of the application of thesystem e-filing, tax knowledge and tax sanctions on taxpayer compliance at KPP Pratama Medan Polonia with tax socialization as a moderating variable. This type of research is associative research with a quantitative approach. The population used in this study are registered taxpayers who submit annual tax returns at KPP Pratama Medan Polonia. The sampling technique usedmethod random sampling with a sample of 100 respondents. The method of analysis of this research is using multiple linear regression and Moderated Regression Analysis